Alcances y limitaciones de la jurisdicción indígena en el Ecuador - Tiban Guala, Marco Roberto (2016)
This research, entitled: "SCOPE AND LIMITATIONS OF INDIGENOUS JURISDICTION IN ECUADOR" faces several edges, on the one hand, the legal and social problem when the daily practice of this right which is fully recognized and enacted in the constitutional and legal provisions, on the other hand the obvious and permanent violation of the indigenous jurisdictional exercise by the authorities of the ordinary courts or laws requiring secondary rules for application and rights holders wield direct exercise of jurisdiction indigenous. In this context, indigenous communities, on the one hand, are fully exercising this right, applying the jurisdictional exercise, and consequently with the sanctions achieve social control in their territories, this action has deserved Legal reactions of various kinds in the country therefore you raised this fundamental problem of understanding, coordination and cooperation that should exist between indigenous and ordinary jurisdictions in the constitutional rule of law, justice, intercultural and plurinational, as is ours. The same, although there precedents mandatory jurisprudence, has not yet been resolved and many call for a secondary law for the full exercise of judicial functions. This paper has been developed based on an extensive theoretical analysis that brings the study of ideas, opinions, doctrines, constitutional, legal and regulatory law Ecuadorian legal norms, jurisprudence and comparative law, along with the results obtained by the application of the techniques of survey and interview, that gather the necessary evidence to support the filing of a legal proposal is to present a bill for cooperation and coordination between the Indian and Justice based on the regular courts Art. 171 final clause of the constitution of the Republic.